GAMBARAN KOLESTEROL TOTAL PADA ORANG YANG KURUS - Ardiansah Hasin; Asni Hasanuddin; Dian Hardianti (Jurnal Media Laboran, 2019)
Cholesterol is a blood fat that is synthesized in the liver and is found in red blood cells, cell membranes, and muscles. In thin people there can be an increase in total cholesterol levels in the blood. Increased Total Cholesterol in thin people is inseparable from the factors of food consumed that have high cholesterol levels, such as foods with saturated fats (lemakhew ani). When these types of foods are continuously consumed in the long run, cholesterol levels in the body will increase even though also does not look fat. However, there are several other factors that affect total cholesterol levels in the blood such as genetic factors, diet and lack of exercise. The purpose of this study was to determine total cholesterol levels in thin people. This type of research uses laboratory observational research that is to determine total cholesterol levels in thin people. The results were tabulated in the form of examination data tables of 20 samples, obtained results that were normal <200 mg / dl of 14 people and high total cholesterol levels> 200 mg / dl of 6 people. From the results of research conducted there is an increase in total cholesterol levels in thin people. In order for thin people to consume fibrous foods, reduce foods that contain lots of fat and increase food portions and frequency of eating.